Os gastos públicos com pessoal e sua relação com a proximidade das eleições – uma análise empírica para os municípios cearenses no período de 2009 a 2016 - Scarano, Bruno Caminha (2018)
The present study aims to evaluate some of the impacts and effects of the proximity of the electoral period in the execution of personnel expenses in the municipalities of the State of Ceará. The analysis of the influence on public spending, in the year of election and in the foregoing, stems directly from the performance and decision making by the head of the municipal executive power, considering the possibility of adopting policies that have the purpose of favoring the obtaining of votes in the election process. As a result of this possibility, it is possible to carry out an analysis about the variation of the public expenditure with personnel in relation to the proximity of the electoral year, given the hypothesis that the government can use the public machine for the purpose of favoring or facilitating its reelection or the one chosen to provide support. The research refers to the analysis of the growth of municipal public expenditures with personnel due to the proximity of the electoral process, in order to analyze the variation and effects of the modification of the amount of this expense in the municipalities of Ceará. The analysis was based on a linear regression model, using panel data, specifically for the period from 2009 to 2016. Analysis was also made of the effect on public expenditure execution due to the political alignment of the mayor with the governor of State, in order to verify the influence of the political adjustment in relation to the personnel expenditure. Among the results obtained, it is verified that the municipal mayors tend to adopt a policy of increasing personnel expenses during the term of office, especially in the years closest to the elections. What is found is that the closer to the electoral process, the greater the public expenditure on personnel, so that it tends to grow from the second year in office. In addition, public expenditure on personnel suffers a considerable change due to the fact that the mayor is aligned with the governor, having a lower growth when compared to municipalities where there is no alignment.